Genomic and transcriptomic insights into legume-rhizobia symbiosis in the nitrogen-fixing tree Robinia pseudoacacia - Hu, Bin (The New phytologist, 2025)
© 2025 The Author(s). New Phytologist © 2025 New Phytologist Foundation.